The Effect of Elementary Grade Retention on Subsequent School Achievement and Ability - Westbury, Marilyn (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
This study compared the achievement and ability of a group of retained elementary students with that of a group of continually promoted elementary school students. The two samples were matched on the basis of gender, school entry reading achievement, grade, and regular school program. Short-term and long-term comparisons between the groups were made using Grade 1 Edmonton Public Schools’ Reading Comprehension Test scores, Grade 3 and Grade 6 Canadian Cognitive Ability Test (CCAT) scores, and Grade 6 subject matter achievement tests. The author concluded that grade retention was inef- fective for improving achievement and ability. Cet article traite d’une étude qui comparait le rendement et les aptitudes d’un groupe de doubleurs au primaire avec celles d’un groupe d’élèves continuellement promus d’une classe à l’autre, également au primaire. Les deux échantillons ont été appariés en tenant compte du sexe, de l’aptitude à la lecture à l’entrée à l’école et de la classe; tous les élèves étaient inscrits dans le programme scolaire ordinaire. Des comparaisons à court terme et à long terme ont été effectuées entre les deux groupes à l’aide du Grade 1 Edmonton Public School’s Comprehension Test, du Grade 3 and Grade 6 Cognitive Ability Test (CCAT) et de divers tests de rendement ayant aux matières de la 6e année. L’auteure conclut que le redoublement n’améliore ni le rendement de l’élève ni ses aptitudes.